Educational attainment and psychological distress among working-age adults in the United States - Ismael G. Muñoz; Alexis R. Santos-Lozada (Elsevier, 2021)
This study builds on a growing body of literature analyzing the education-health gradient across detailed educational categories, which documents that US working-age adults who attended college but did not earn a bachelor's degree report equal or worse health than adults with a high school diploma. This is known as the "anomaly" in the education-health gradient. The purpose of this study is to test whether this pattern extends to measures of serious psychological distress (SPD) and individual symptoms by using data from the National Health Interview Survey (NHIS, 1997-2018) and a series of logistic regression models. We find that the anomaly in the education-health gradient is present for a summary measure of SPD as well as for five of the six symptoms that make up this measure. The exception was reporting feeling sad most or all the time during the last month, where adults with "some college" were found to have lower odds than those with a high school diploma. Further stratified analysis by sex revealed that this result for feeling sad was driven by women. In terms of associate degrees, our models show that adults with a vocational/technical associate degree have statically similar odds of SPD and reporting four out of six symptoms (exceptions were feeling hopeless and sadness), while those with an academic associate degree have significantly lower odds in all outcomes. The robustness of the models used is supported by an extensive sensitivity analysis. Overall, we find evidence of the anomaly in the education-health gradient in SPD and individual symptoms of psychological distress at the sub-baccalaureate level, adding to previous studies that document the anomaly in markers of physiological dysregulation, health conditions, vision problems, functional limitations, and pain.